1996
DOI: 10.1242/jcs.109.6.1369
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin regulates calvarial osteoblast differentiation

Abstract: The secretion of fibronectin by differentiating osteoblasts and its accumulation at sites of osteogenesis suggest that fibronectin participates in bone formation. To test this directly, we determined whether fibronectin-cell interactions regulate progressive differentiation of cultured fetal rat calvarial osteoblasts. Spatial distributions of alpha 5 integrin subunit, fibronectin, osteopontin (bone sialoprotein I) and osteocalcin (bone Gla-protein) were similar in fetal rat calvaria and mineralized, bone-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…These results collectively confirm the role of MSC-secretome in inducing bone regen eration, according to previously published research studies [43][44][45][46][47][48]. This effect mainly de pends on the osteogenic factors revealed in Lyosecretome by proteomic characterization [21], such as fibronectin [49], alpha-2-macroglobulin [50], apolipoprotein A [51], and TGF β [52]. Of note, the MSC-secretome employed in this work was formulated as a ready-to use, freeze-dried pharmaceutical dosage form, which can be easily adapted by the clinica community.…”
Section: Resultssupporting
confidence: 89%
“…These results collectively confirm the role of MSC-secretome in inducing bone regen eration, according to previously published research studies [43][44][45][46][47][48]. This effect mainly de pends on the osteogenic factors revealed in Lyosecretome by proteomic characterization [21], such as fibronectin [49], alpha-2-macroglobulin [50], apolipoprotein A [51], and TGF β [52]. Of note, the MSC-secretome employed in this work was formulated as a ready-to use, freeze-dried pharmaceutical dosage form, which can be easily adapted by the clinica community.…”
Section: Resultssupporting
confidence: 89%
“…Fibronectin plays an important role in osteoblast morphogenesis, differentiation, and mineralization. 33 The distribution pattern of FN is indicative of osteoblast's ability to synthesize, mineralize, and organize the extracellular matrix, irrespective of the nature of the system (GO, HAP-GO, HAP-CS-GO) (Fig. 6).…”
Section: Cell Culture Studiesmentioning
confidence: 99%
“…13,14 In addition, Fn has been localized in the periosteum of rat calvaria 15 and in the osteoid surrounding implants. 16 These studies raise the question whether Fn could guide early stages of osteogenic differentiation. In vitro studies have revealed that the effects of Fn on hMSC physiology are complex: Fn-coated biomaterials promoted hMSC attachment 17,18 and culture of hMSCs on Fn-coated surfaces promoted their migration, adhesion and proliferation, however, it did not affect their osteogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%